Analyse and Survey Variables of Macroeconomic Effects on Credit Risk of Bank Mellat - Ghahroud, Majid Lotfi; Amini, eNSIEH (European Journal of Economics and Business Studies, 2016)
Trying to identify, measure and manage credit risk in the banking system is crucial. Given that on the one hand financing system of the country is bank-based and on the other hand lack of proper investigation in the credit risk area lead to a reduction in the allocation of resources in the form of loans and has been increased the non-performing loan. Therefore, concerning about credit risk and its reduction strategies has grown. In this study attempted to examine the impact of macro-economic features, such as GDP, inflation, rate of GDP growth, imports goods and final services, rate of nominal interest, amount of credit risk in the last period and the growth rate of facility to be addressed in Credit risk of the Mellat Bank.Moreover, the effects of macroeconomic conditions on credit risk are investigated. In this regard, credit risk of 52 active branches of Mellat Bank with variables such as GDP growth, GDP rates, inflation ,credit growth and nominal interest rate since 1386 to 1391 has been measured by using panel data. To do this, combination of cross-sectional and time-series data (panel data) are used. That means relation between the variables evaluated and tested by using econometric methods such as data compilation methodology (panel data). To estimate the model, to select the best model of conventional panel data, fixed effects and random effects, the F and Housman tests will be done. In this regard, E-views software utilized and Excel for calculation of variables has been used. Based on the results of research the effect of nominal interest rate, facility growth rate and the grow rate of GDP on the credit risk is significant and positive in contrast, the inflation rate has had a negative effect on credit risk.